2019
DOI: 10.5194/hess-23-4433-2019
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood and stand structure affect stemflow generation in a heterogeneous deciduous temperate forest

Abstract: Abstract. Although stemflow oftentimes only represents a small portion of net precipitation in forests, it creates hot spots of water input that can affect subsurface storm-flow dynamics. The distribution of stemflow over different trees is assumed to be temporally stable, yet often unknown. Therefore, it is essential to know the systematic factors driving stemflow patterns. Several drivers have been identified in the past, mainly related to tree traits. However, less attention has been paid to tree neighbourh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 51 publications
1
19
1
Order By: Relevance
“…Some studies have suggested there is a threshold of rainfall amounts before initiating stemflow (Levia & Frost, 2003;Metzger et al, 2019;. In our study, Q. acutissima did not produce any stemflow in four rainfall events (G P < 4.4 mm), even though B. papyrifera generated stemflow in all events (n = 9) of rainfall type D. This result indicated stemflow from Q. acutissima trees had a higher threshold of rainfall amounts than B. papyrifera trees.…”
Section: Effects Of Tree Species On Stemflow Dynamics Depend On Raicontrasting
confidence: 45%
See 3 more Smart Citations
“…Some studies have suggested there is a threshold of rainfall amounts before initiating stemflow (Levia & Frost, 2003;Metzger et al, 2019;. In our study, Q. acutissima did not produce any stemflow in four rainfall events (G P < 4.4 mm), even though B. papyrifera generated stemflow in all events (n = 9) of rainfall type D. This result indicated stemflow from Q. acutissima trees had a higher threshold of rainfall amounts than B. papyrifera trees.…”
Section: Effects Of Tree Species On Stemflow Dynamics Depend On Raicontrasting
confidence: 45%
“…In addition, because stemflow has the ability to transport nutrients, "fertile islands" may form around tree boles (Imamura et al, 2017;Loffredo et al, 2014), which would affect the growth and distributions of understory vegetation (Andersson, 1991;Falkengren-Grerup, 1989). Therefore, it is important to investigate stemflow dynamics to gain a better understanding the hydrological and biogeochemical processes in forest ecosystems (Metzger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the structure of canopies can influence how effectively individual trees drain this capture rainfall, and currently it is hypothesized that there may be an optimum branch inclination angle that most efficiently drains rainwater to the stem (Levia, 2003;Sadeghi et al, 2020). Third, the orientation of canopies within the "tree neighborhood" is believed to impact stemflow generation -some dominant canopies overshadow others (Metzger et al, 2019) or gather wind-driven rainfall (Herwitz and Slye, 1995;Levia and Herwitz, 2005;Van Stan et al, 2011). Finally, bark structure, being the surface over which stemflow must flow, is considered a master variable.…”
Section: Introductionmentioning
confidence: 99%